2022
DOI: 10.1091/mbc.e22-04-0117
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tolerance to multiple environmental stresses due to limitation of structural diversity of complex sphingolipids

Abstract: Structural diversity of complex sphingolipids is important for the maintenance of various cellular functions. It is shown that the more the structural variation of complex sphingolipids is limited, the more sensitivity to various environmental stresses tends to increase, which is caused by impaired integrity of plasma membranes and cell walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…Thus, it is most likely that the hypersensitivity to CFW in SPH cells reflects impairment of cell wall integrity. Yeast cells with loss of structural diversity of complex sphingolipids exhibit hypersensitivity to elevated temperature due to damage to cell walls [21,46]. As compared with PHS cells, SPH cells also show hypersensitivity to 39 °C without rhodamine 6G incorporation efficiency being affected (Figs 4E,L and 5J), supporting the notion of impaired cell wall integrity in SPH cells.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Thus, it is most likely that the hypersensitivity to CFW in SPH cells reflects impairment of cell wall integrity. Yeast cells with loss of structural diversity of complex sphingolipids exhibit hypersensitivity to elevated temperature due to damage to cell walls [21,46]. As compared with PHS cells, SPH cells also show hypersensitivity to 39 °C without rhodamine 6G incorporation efficiency being affected (Figs 4E,L and 5J), supporting the notion of impaired cell wall integrity in SPH cells.…”
Section: Discussionmentioning
confidence: 74%
“…5A). Previously, we found that loss of structural diversity of complex sphingolipids, which causes hypersensitivity to multiple environmental stresses, does not also cause significant change of plasma membrane permeability; however, the loss of diversity increases the permeability under several stress conditions [21]. As compared with PHS cells, SPH cells exhibited hypersensitivity to NaCl, sorbitol, pH 3.5, pH 7.5, sorbic acid, high temperature, SDS, and CFW (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, a high-content microscopy screen identified Cvm1 as a protein located at sites where the membrane of the yeast vacuole (which, it should be recalled is the equivalent of a mammalian lysosome [ 200 , 201 ]) contacts three other organelles: mitochondria; peroxisomes; and, the ER emanating from the nuclear envelope [ 202 ]. Changes in the level of Cvm1 alters the levels of multiple sphingolipid classes, which can reduce the tolerance of yeast cells to various environmental stresses [ 203 ], and the contact sites containing Cvm1 are elevated when sphingolipid production is compromised [ 202 ]. The central segment of Cvm1 (residues 244–558) has a strongly predicted homology to the α–β hydrolase fold.…”
Section: Functions Of Ypk1mentioning
confidence: 99%